Is The CEO’s Ego Driving Profits? Uncovering The Relationship Between Narcissism and Earnings Management - Putri, Belinda Regina; Suryani, Ani Wilujeng (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
Globalization intensifies competition, pressuring profit margins and challenging companies to outperform competitors. This demands precise decision-making by Chief Executive Officers (CEOs), whose personalities influence their perceptions and strategies. This study examines the impact of CEO narcissism and tenure length on earnings management in 180 manufacturing companies listed on the IDX during 2015–2019. Using Generalized Least Square regression, the findings reveal that CEO narcissism, measured through photographs in annual reports, positively affects earnings management, while tenure length has no significant impact. By analyzing visual elements in annual reports as a proxy for narcissistic traits, this research offers a novel lens to explore how CEO psychology drives financial decisions. The results suggest narcissistic CEOs are more likely to manipulate earnings to gain recognition and validation. Investors should therefore assess management personalities through annual reports alongside financial metrics to make informed investment decisions.